1984
DOI: 10.1111/j.1528-1157.1984.tb03466.x
|View full text |Cite
|
Sign up to set email alerts
|

Progabide Treatment in Severe Epilepsy: A Double‐Blind Cross‐over Trial Versus Placebo

Abstract: Twenty therapy-resistant epileptic patients entered a double-blind, randomized, two-period, cross-over trial comparing progabide (19.3-36 mg/kg/day) and placebo as add-on drugs to standard therapy. Each period lasted 6 weeks with a gradual crossover during 4 days. Five patients were dropped because of reasons unrelated to treatment. Among the 15 patients who completed the study, seven had partial, six primary generalized, and two secondary generalized epilepsies. Preexisting antiepileptic drugs (AEDs) ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The efficacy of PGB in the treatment of seizures has been variable. In some studies (Van der Linden et al, 1981;Loiseau et al, 1983;Weber et al, 1983;Martinez-Lage et al, 1984), PGB was clearly more effective than placebo or other standard treatment. Some of these studies formed the basis for recognition of PGB as a drug with sufficient safety and efficacy to warrant approval €or marketing in France.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The efficacy of PGB in the treatment of seizures has been variable. In some studies (Van der Linden et al, 1981;Loiseau et al, 1983;Weber et al, 1983;Martinez-Lage et al, 1984), PGB was clearly more effective than placebo or other standard treatment. Some of these studies formed the basis for recognition of PGB as a drug with sufficient safety and efficacy to warrant approval €or marketing in France.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the European clinical trials have shown it to be effective (Van der Linden et al, 1981;Loi-seau et al, 1983;Weber et a]., 1983;Martinez-Lage et al, 1984), while results of other studies have been less favorable (Dam et al, 1983;Schmidt, 1984). PGB was the first drug to be tested by the Epilepsy Branch of the National Institutes of Health (NIH) under the Antiepileptic Drug Development Program (Leppik et al, 1985).…”
mentioning
confidence: 99%
“…In animal studies, PGB has a wide spectrum of anticonvulsant actions, but little evidence exists for a mechanistic relationship to GABA systems. Several open-label uncontrolled studies suggested efficacy and safety of PGB in a variety of seizure types (Martinez-Lage et al, 1984;Benassi et al, 1988), but other studies in partial (Dam et al, 1983) and absence (Stefan et al, 1988) seizures failed to show benefit. The usual dosage range in clinical trials has been about 15-60 mg/kg/day (Schmidt and Utech, 1986).…”
Section: Progabide (Pgb)mentioning
confidence: 99%
“…The usual dosage range in clinical trials has been about 15-60 mg/kg/day (Schmidt and Utech, 1986). Several open-label uncontrolled studies suggested efficacy and safety of PGB in a variety of seizure types (Martinez-Lage et al, 1984;Benassi et al, 1988), but other studies in partial (Dam et al, 1983) and absence (Stefan et al, 1988) seizures failed to show benefit. Two controlled studies of PGB as an add-on demonstrated unimpressive efficacy (Schmidt and Utech, 1986;Leppik et al, 1987).…”
Section: Progabide (Pgb)mentioning
confidence: 99%
“…In both open pilot studies and placebocontrolled studies, progabide appeared to be an effective antiepileptic drug with a broad spectrum of action [1][2][3][4]7].…”
Section: Introductionmentioning
confidence: 99%